Exploring the resilience skills and strategies of social workers - Lucy R. Mangolele; Taetske M. Calitz (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Research shows that social workers face numerous challenges because of the demanding nature of their profession, necessitating the development of resilience skills and techniques. Social workers assist marginalised populations and operate in challenging environments, requiring strong resilience strategies.